APLIKASI MODEL KANO UNTUK ANALISIS KEBUTUHAN INFORMASI HARGA PADA E-TOURISM - Luh Gede Surya Kartika; I Komang Rinartha Yasa Negara (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
Price information on the e-toursim website is important, because it can be used as a reference for making travel decisions. However, until now there has been no research on the need for price information and especially on e-tourism. Confirmation of the need for price information on e-tourism will lead to the effect of this functionality on satisfaction and disappointment ofe-tourism users. This study uses the Kano model to determine the functional needs of price information on e-tourism. The result obtained is that the functionality of price information is an important quality that must be possessed by an e-tourism website. The Kano category for all pricing information sub functionalities is “Must”. This means that the sub-functionality of tour package price information, tourist activity price information, entrance ticket price information, and transportation price information on e-tourism are functional attributes that can reduce user satisfaction if they are not displayed properly. However, if the price information has been displayed properly, then it will increase user satisfaction significantly because respondents think that price information on e-tourism should exist and the performance is good